PROGRESS OF FORMS AND CONTENT OF THE FINANCIAL STATEMENTS IN ACCORDANCE WITH THE REQUIREMENTS OF NATIONAL AND INTERNATIONAL STANDARDS - E. Kusch; S. Chuzhinov (Вестник университета)
Thе article provides a brief description of accounting. We consider the process of reform and transformation of the accounting system in the Russian Federation for a period of time in several stages.